2012
DOI: 10.1038/ejhg.2012.204
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variant in the telomerase gene modifies cancer risk in Lynch syndrome

Abstract: Lynch syndrome (LS) is an inherited cancer-predisposing disorder caused by germline mutations in the mismatch repair (MMR) genes. The high variability in individual cancer risk observed among LS patients suggests the existence of modifying factors. Identifying genetic modifiers of risk could help implement personalized surveillance programs based on predicted cancer risks. Here we evaluate the role of the telomerase (hTERT) rs2075786 SNP as a cancer-risk modifier in LS, studying 255 and 675 MMR gene mutation c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 44 publications
1
18
0
Order By: Relevance
“…A recent study of 930 MMR gene mutation carriers reported no overall difference in genotype frequencies between carriers affected and unaffected with CRC for the rs2075786 SNP in hTERT (RR=2.46; 95% CI=0.78–7.82) [ 10 ], a finding that is consistent with ours. This study also reported marginally significant evidence of association between the AA genotype of the rs2075786 SNP and cancer risk for carriers diagnosed with Lynch syndrome related-cancer diagnosed before the age of 45 years (RR=2.90; 95% CI=1.02–8.26; p=0.05) but we found no evidence of an association for that SNP and CRC risk before age 45 years.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…A recent study of 930 MMR gene mutation carriers reported no overall difference in genotype frequencies between carriers affected and unaffected with CRC for the rs2075786 SNP in hTERT (RR=2.46; 95% CI=0.78–7.82) [ 10 ], a finding that is consistent with ours. This study also reported marginally significant evidence of association between the AA genotype of the rs2075786 SNP and cancer risk for carriers diagnosed with Lynch syndrome related-cancer diagnosed before the age of 45 years (RR=2.90; 95% CI=1.02–8.26; p=0.05) but we found no evidence of an association for that SNP and CRC risk before age 45 years.…”
Section: Discussionsupporting
confidence: 89%
“…Using data from the International HapMap project ( http://www.HapMap.org ) and Haploview program (version 3.12) and a minimum r 2 threshold of 0.8 we identified a set of tagging SNPs to capture the genetic variation in the hTERT gene. SNPs previously associated with CRC risk [ 8 , 9 , 17 ] or from the single study of CRC risk in MMR gene mutation carriers [ 10 ] were also genotyped. The selected SNPs ( Supplementary Table 1 ) were genotyped using Sequenom's iPLEX Gold.…”
Section: Methodsmentioning
confidence: 99%
“…a risk modifier. This is supported by our recent observation that a variant in the telomerase gene, hTERT , increases cancer risk in young LS patients (<45 years of age), as it is associated with shortened telomeres in cancer-affected MMR gene mutation carriers [11]. Further studies assessing telomere length before and after cancer diagnosis in CRC patients will provide a definitive answer regarding the suggested effect of cancer on telomere length in blood cells.…”
Section: Discussionmentioning
confidence: 57%
“…Moreover, we have recently shown that a common genetic variant located in the telomerase gene ( hTERT ; MIM 187270) increases cancer risk in LS patients at early ages, and that this SNP is associated with shortened telomere length in cancer-affected MMR gene mutation carriers [11]. Telomeres consist of multiple short repeats (TTTAGG) at the ends of chromosomes and protect them against large-scale genomic rearrangements.…”
Section: Introductionmentioning
confidence: 99%
“…6163 Recent associations have also been made between genes regulating the cell cycle, xenobiotic-metabolizing enzymes, and telomerase and young age of CRC onset in MMR gene mutation carriers. 6466 …”
Section: Clinical Features and Cancer Risks In Lynch Syndromementioning
confidence: 99%